2022
DOI: 10.1111/1460-6984.12804
|View full text |Cite
|
Sign up to set email alerts
|

The true cost of dysphagia on quality of life: The views of adults with swallowing disability

Abstract: Background: Dysphagia impacts negatively on quality of life, however there is little in-depth qualitative research on these impacts from the perspective of people with dysphagia.Aims: To examine the lived experiences and views of people with lifelong or ongoing dysphagia on the impacts of dysphagia and its interventions on quality of life, and barriers and facilitators to improved quality of life related to mealtimes. Methods & Procedures: Nine adults with lifelong or acquired chronic dysphagia engaged in in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…This is stricter than the approach in Carnaby et al [ 13 ] in which up episodes of clinical signs of aspiration of up to 40% are accepted before reversion [ 14 ]. Since enjoyment and feeling safe without aspiration during ingestion and mealtimes are perceived as essential in older adults with OD [ 52 ], the strict criterion in the ACT-ING program might have contributed to the intervention tolerance, perceived usability, and acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…This is stricter than the approach in Carnaby et al [ 13 ] in which up episodes of clinical signs of aspiration of up to 40% are accepted before reversion [ 14 ]. Since enjoyment and feeling safe without aspiration during ingestion and mealtimes are perceived as essential in older adults with OD [ 52 ], the strict criterion in the ACT-ING program might have contributed to the intervention tolerance, perceived usability, and acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia has a significant effect on the quality of life, with contributing factors including poorer mealtime experiences and feelings of loss of choice [38]. Carer burden and dysphagia have received attention recently.…”
Section: Carer Burden Dysphagia and Nutritionmentioning
confidence: 99%
“…However, at long-term follow-up (12–72 months), resolution of the swallowing difficulties was seen in one-third of these patients [ 28 ]. Efforts to predict and prevent postoperative dysphagia are crucial as this complication has been associated with prolonged hospital stay, reduced health-related quality of life (HRQoL) [ 25 ], and increased mortality [ 3 , 11 , 12 , 20 , 27 , 30 ]. In a systematic review, several pre- and post-operative radiographic measurements were found to correlate with the occurrence of dysphagia in patients undergoing OCF [ 28 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%